IDENTIFYING STUDENTS MISCONCEPTIONS ON CHEMICAL BONDING USING TWO TIER TEST - Nahadi, Nahadi; Hernani, Hernani; Agustini, Nurlaela (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Misconception is one of the obstacles that may reduce learning effectiveness. In this study, we develop two-tier multiple choice diagnostic test instrument that can be used to identify students’  misconceptions on chemical bonding. Two-tier test with 25 test items was proven to be valid and reliable. This diagnostic test was able to detect students’ misconceptions including misconceptions about element stability, ionic bonding, covalent bonding, covalent coordinate bonding, metallic bonding, as well as characteristics and physical property of each bonding. The identified misconceptions could serve as a reference for teachers in remediating students’ misconception.